Hemostasis and nanotechnology - Hangge, Patrick; Stone, Jonathan; Albadawi, Hassan; Zhang, Yu Shrike; Khademhosseini, Ali; Oklu, Rahmi (Cardiovascular Diagnosis and Therapy, 2017)
Hemorrhage accounts for significant morbidity and mortality. Various techniques have been employed to augment hemostasis from simple tourniquets to self-assembling nanoparticles. A growing understanding of the natural clotting cascade has allowed agents to become more targeted for potential use in different clinical scenarios. This review discusses current and developing hemostatic techniques, including matrix agents, external agents, biologically inspired agents, and synthetic and cell-derived nanoparticles.